Cycadophila, a new genus (Coleoptera: Erotylidae: Pharaxonothinae) inhabiting Cycas debaoensis (Cycadaceae) in Asia - Xu, Guang; Tang, William; Skelley, Paul; Liu, Nian; Rich, Stephen (Zootaxa, 2015)
Asian species assigned to Pharaxonotha Reitter formed a separate clade from New World species of the genus and are distinguished on the basis of morphology and analysis of 16S rRNA gene sequences. Cycadophila, new genus, is described based on a consideration of four Asian species in comparison with New World Pharaxonotha. This new genus includes two new species (Cycadophila debaonica new species and Cycadophila fupingensis new species) and two previously described species (Cycadophila nigra (Gorham) new combination and Cycadophila yunnanensis (Grouvelle) new combination). These latter two may represent species complexes. Lectotypes are designated for Thallis nigra Gorham and Pharaxonotha yunnanensis Grouvelle. Larvae of C. debaonica and C. fupingensis are described based on individuals collected on the cones of Cycas debaoensis Y. C. Zhong & C. J. Chen (Cycadaceae), a cycad native to Guangxi and Yunnan provinces, China.